Factors Influencing Antenatal Haematinics Prescription Behaviour of Physicians in Calabar, Nigeria - Akpan, Ubong Bassey; Agan, Thomas Udagor; Monjok, Emmanuel; Okpara, Chinedu; Etuk, Saturday (Open access Macedonian journal of medical sciences, 2017)
BACKGROUND: Routine iron and folic acid supplementation in pregnancy have been proved to be effective in reducing the prevalence and morbidities of anaemia. However, there is limited data regarding the prescription habits of physician obstetric care givers.AIM: This study set to investigate the attitudes and factors which influence the practice among physicians in University of Calabar Teaching Hospital (UCTH).MATERIAL AND METHODS: A questionnaire based cross-sectional survey was conducted among randomly recruited physician offering antenatal services between August and September 2015. Systemic sampling was used to select 70 doctors in the departmental duty roster. Data were presented in percentages and proportion. Chi-square test was used to test the association between variables. Statistical significance was set at p < 0.05.RESULTS: The response rate was 100%. The mean age of the respondents was 30.26 Â± 6.67 years. All the respondents routinely prescribed haematinics to pregnant women but 34.3% of them did not prescribe to apparently healthy clients in their first trimester. Only 30% and 11.4% of them prescribed it in the postnatal and preconception periods respectively. Brands that contained iron, folate and vitamins as a single capsule were mostly favoured, and information about brands of drugs was mostly provided by the pharmaceutical sales representatives. Younger doctors were more likely to offer haematinics with nutritional counselling compared to older respondents. However, there was no significant relationship between haematinics prescription and sex (p = 0.3560), Age (p = 0.839), current professional status (p = 0.783), and client complaint of side effect of medication (p = 0.23). Oral medication was mostly utilised.CONCLUSION: Effort to effectively control anaemia in pregnancy should involve re-orientation of physician obstetric care providers especially about prenatal and postnatal medication and counselling.